2018
DOI: 10.1155/2018/1801243
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin‐Induced Oxidative Stress Leads to DNA Damage in the Cerebellum of Hyperbilirubinemic Neonatal Mice and Activates DNA Double‐Strand Break Repair Pathways in Human Cells

Abstract: Unconjugated bilirubin is considered a potent antioxidant when present at moderate levels. However, at high concentrations, it produces severe neurological damage and death associated with kernicterus due to oxidative stress and other mechanisms. While it is widely recognized that oxidative stress by different toxic insults results in severe damage to cellular macromolecules, especially to DNA, no data are available either on DNA damage in the brain triggered by hyperbilirubinemia during the neonatal period or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 70 publications
4
33
1
1
Order By: Relevance
“…In the present study, pathological increase in bilirubin level, irrespective of its neurotoxic properties, activated diminishing mechanisms of oxidative stress and declined the pro-oxidantantioxidant balance of the body. This means that even a pathologic increase of bilirubin leads to an increase of antioxidants levels, which can be detected in laboratory tests; it stays in contrast to the previous studies which reported antioxidant properties only for the physiologic amounts of the bilirubin (8,24,25).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In the present study, pathological increase in bilirubin level, irrespective of its neurotoxic properties, activated diminishing mechanisms of oxidative stress and declined the pro-oxidantantioxidant balance of the body. This means that even a pathologic increase of bilirubin leads to an increase of antioxidants levels, which can be detected in laboratory tests; it stays in contrast to the previous studies which reported antioxidant properties only for the physiologic amounts of the bilirubin (8,24,25).…”
Section: Discussioncontrasting
confidence: 56%
“…Dani et al (24) in another research stated that the antioxidant effects may be observed only in the physiologic amount of the bilirubin, and that its pathologic levels are associated with pro-oxidant effects. Similar to the mentioned articles, another investigation performed by Rawat et al (25) in neonatal mice declared that the potent antioxidant effect of the bilirubin was only observed at the moderate levels and it had pro-oxidant effects at high con-centrations. Furthermore, in contrast to our results, they attributed the neurotoxic effects of the bilirubin to oxidative stress and other mechanisms (25).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The symptoms mentioned above are likely brought on by low blood pressure and a hypercoagulation state by the direct and indirect action of SARS-Cov-2. Also, acidosis, high lactate, or hyperbilirubinemia have also been observed in most patients, which are all features related with oxidative stress mechanisms [ 102 , 103 ] and antioxidant responses [ 104 ]. Severe COVID-19 patients with developed typical clinical manifestations of septic shock, such as serum lactate levels >2 mmoL L −1 and persistent hypotension despite fluid resuscitation, generally require vasopressors to maintain MAP ≥ 65 mm Hg [ 105 ].…”
Section: Critically Ill Covid-19 Patients Show Clinical Manifestatmentioning
confidence: 99%
“…However, we reported that concentrations of 100 and even 10 nM Bf may cause oxidative stress and injury to neocortical synaptosomes after 4 h of incubation (Brito et al, 2004). Recently, 24 h and 48 h treatment with 70 nM and 140 nM Bf compromised the cell viability of SH-SY5Y human cells and the highest concentration caused oxidative stress and DNA damage (Rawat et al, 2018). Such protective and neurotoxic distinct effects may associate to different cell types and culture models used by the researchers.…”
Section: Introductionmentioning
confidence: 93%